The Roots of “Penal Populism”: the Role of Media and Politics - DOBRYNINA, MARGARITA (Kriminologijos studijos, 2017)
Penal populism is often labeled as a process whereby politicians devise punitive penal policies, which are adjudged to be “popular” within the general public, and are designed to mobilize votes rather than improve the crime and justice situation. A “tough on crime” policy stance is usually most manifest during election campaigns. [...]